2007
DOI: 10.1002/chp.110
|View full text |Cite
|
Sign up to set email alerts
|

Developing an instrument to measure bias in CME

Abstract: The tool and the data from this study can be used to raise awareness about bias in CME. Policymakers can use this tool to ensure that CME providers meet the standards for education, and CME providers can use the tool for conducting random audits of events they have accredited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Given that commercial influence is often subtle, a single binary question may fail to fully capture the range of learner perceptions of commercial influence 25. Moreover, learner perceptions of bias may not precisely correspond to actual bias in CME activities.…”
Section: Discussionmentioning
confidence: 99%
“…Given that commercial influence is often subtle, a single binary question may fail to fully capture the range of learner perceptions of commercial influence 25. Moreover, learner perceptions of bias may not precisely correspond to actual bias in CME activities.…”
Section: Discussionmentioning
confidence: 99%
“…Review articles were analyzed with a validated instrument for monitoring bias in CME [56]. The Takhar instrument consisted of 13 questions (see Table 1), with scores graded on a scale from 1 (strongly disagree this paper displays bias) to 4 (strongly agree this paper displays bias), or N/A (not applicable).…”
Section: Methodsmentioning
confidence: 99%
“…In our initial developmental study, we found that Phase I content review was able to distinguish between biased and unbiased events; 8 however, inter-rater reliability between content reviewers was not assessed. In addition, our initial reliability study demonstrated evidence of good internal consistency (Cronbach's α = 0.82) and good inter-rater reliability (intraclass correlation or ICC = 0.67) among a small set of raters.…”
Section: Bias Management Processmentioning
confidence: 98%
“…In addition, our initial reliability study demonstrated evidence of good internal consistency (Cronbach's α = 0.82) and good inter-rater reliability (intraclass correlation or ICC = 0.67) among a small set of raters. 8 In the current study, reliability among multiple raters who were located across a variety of centers and were trained using distance education technology was assessed.…”
Section: Bias Management Processmentioning
confidence: 99%
See 1 more Smart Citation